Millennial consumers in the convenience food market = Konsumenci generacji Y na rynku żywności wygodnej - Barska, Anetta (Zielona Góra: Faculty of Economics and Management Press)
The demand for food products is gradually increasing, which is why understanding consumer behavior in the convenience food market is an important issue. Knowledge in this field may be useful in the process of developing marketing strategies. The purpose of the article is to present the attitude towards convenience food of the representatives of Generation Y (also known as millennials). Literature analysis and results of the author's own surveys were used in the research proceedings. The research was conducted on a group of 364 millennial consumers living in the border area of Southwestern.
Keywords: żywność wygodna; generacja Y; zachowania konsumenta; analiza korespondencji; badania ankietowe; convenience food; generation Y; consumer behavior; correspondence analysis; survey; Millennials